Clinical and pathological differences between early- and late-onset colorectal cancer and determinants of one-year all-cause mortality among advanced-stage patients: a retrospective cohort study in Medellín, Colombia (2024)
ABSTRACT: Objective: To identify the differences between early- (EOCRC) and late-onset colorectal cancer (LOCRC), and to evaluate the determinants of one-year all-cause mortality among advanced-stage patients. Methods: A retrospective cohort study was carried out. CRC patients ≥ 18 years old were included. Chi-Square test was applied to compare both groups. Uni- and multivariate regressions were performed to evaluate the determinants of one-year all-cause mortality in all advanced-stage patients regardless of age of onset. Results: A total of 416 patients were enrolled; 53.1 % were female. Ninety cases (21.6 %) had EOCRC and 326 (78.4 %) had LOCRC. EOCRC cases were predominantly sporadic (88.9 %). Histology of carcinoma other than adenocarcinoma (p= 0.044) and rectum tumors (p= 0.039) were more prevalent in EOCRC. LOCRC patients were more likely to have smoking history (p < 0.001) and right colon tumors (p = 0.039). Alcohol consumption history (odds ratio [OR]: 3.375, 95 %CI: 1.022-11.150) and stage IV (OR: 12.632, 95 %CI: 3.506-45.513) were associated with higher one-year all-cause mortality among advanced-stage patients, the opposite was noted with left colon tumors (OR: 0.045, 95 %CI: 0.003-0.588). Conclusion: EOCRC was predominantly sporadic and had more cases of uncommon histological subtypes and rectal tumors. LOCRC was characterized by a higher prevalence of smoking history. Multivariate regression revealed an association between higher one-year all-cause mortality and alcohol consumption history and stage IV in advanced-stage patients. CRC exhibited differences based on age of onset. The evaluated factors associated with CRC mortality provide valuable insights for healthcare professionals, emphasizing the importance of adequate clinical assessment and early CRC diagnosis.